Adverse events during minimally invasive esophagectomy in prone position associated with the learning curve - Velasco Hernández, Daniel N.; Horiuchi, Héctor R.; Rivaletto, Lucas A.; Gómez Oro, Carolina; Ortiz, Enrique (Revista Argentina de Cirugía, 2021)
Background: Since the initial description of laparoscopic fundoplication in 1991 for the treatment of gastroesophageal reflux disease, different minimally invasive procedures have been developed until nowadays, when esophagectomy is performed using combined thoracoscopy and laparoscopy. Objective: The aim of our study is to analyze the adverse events of minimally invasive esophagectomy in prone position during the learning curve. Material and methods: Between November 2011 and June 2017, 36 patients underwent minimally invasive esophagectomy in prone position in the Hospital Interzonal General de Agudos (HIGA) San Martín and the Instituto de Diagnóstico de La Plata. Results: During the abdominal stage one patient presented coronary vessel injury. The complications occurring in the thoracic stage included lung injury (n =2), azygos arch injury (n = 1), thoracic duct dissection (n = 1), laryngeal recurrent nerve lesion (n = 1) and main stem bronchus injury (n = 1) during lymph node resection. Most of these complications occurred in the first 20 patients, while in the remaining 16 cases only lung injury occurred (p = 0.10) Conclusion: Minimally invasive esophagectomy in prone position is a feasible and safe procedure that can cause serious intraoperative complications due to its complexity. Although the results of our series did not show statistically significant differences, the number of adverse events during surgeries performed by the same team showed an important reduction associated with better training.